The Effectiveness of the POE2WE Model in Developing Student Character to Face the Challenges of the 21st Century - Wahidin; Nana; Eko Sujarwanto; Samuel Agus Triyanto (GoAcademica Research & Publishing, 2023)
This study aims to assess the character building of students who learn using the POE2WE learning model. Character building, which is the focus of research, is religion, nationalism, integrity, cooperation, and autonomy. The study sample consisted of 170 students from 284 students at Siliwangi University, Galuh University, and Institute of Health Science of Ministry of Health in Tasikmalaya. It was selected using a purposive sampling method. The research method is survey research. The validity and reliability of the instruments were measured using the Alpha Cronbach and Pearson's correlation. The results showed that students have good religious character, nationalism, integrity, cooperation, and autonomy in learning. Meanwhile, there was a relationship between religious character, nationalism, integrity, cooperation, and autonomy in learning. Finally, this study shows that the POE2WE learning model contributes to developing character education for students to face the challenges of the 21st century.